Exsolution and shock microstructures of igneous pyroxene clasts in the Northwest Africa 7533 Martian meteorite. (17th April 2016) - Leroux, Hugues; Jacob, Damien; Marinova, Maya; Hewins, Roger H.; Zanda, Brigitte; Pont, Sylvain; Lorand, Jean‐Pierre; Humayun, Munir
Abstract: Northwest Africa (NWA) 7533 is a Martian regolith breccia. This meteorite (and its pairings) offers a good opportunity to study (near‐) surface processes that occurred on early Mars. Here, we have conducted a transmission electron microscope study of medium‐ and coarse‐grained (a few tens to hundreds of micrometers) Ca‐rich pyroxene clasts in order to define their thermal and shock histories. The pyroxene grains have a high‐temperature (magmatic) origin as revealed by the well‐developed pigeonite–augite exsolution microstructure. Exsolution lamella characteristics (composition, thickness, and spacing) indicate a moderately slow cooling. Some of the pyroxene clasts display evidence for local decomposition into magnetite and silica at the submicron scale. This phase decomposition may have occurred at high temperature and occurred at high oxygen fugacity at least 2–3 log units above the QFM buffer, after the formation of the exsolution lamellae. This corresponds to oxidizing conditions well above typical Martian magmatic conditions. These oxidizing conditions seem to have prevailed early and throughout most of the history of NWA 7533. The shock microstructure consists of (100) mechanical twins which have accommodated plastic deformation. Other pyroxene shock indicators are absent. Compared with SNC meteorites that all suffered significant shock metamorphism, NWA 7533 appears only mildly shocked. The twin microstructure is similar from one clast to another, suggesting that the impact which generated the (100) twins involved the compacted breccia and that the pyroxene clasts were unshocked when they were incorporated into the NWA 7533 breccia.